Attitudes and Experience of Malaysian Parents towards School Closure during the COVID-19 Pandemic - Ting, Chuong Hock; Jeffery Stephen; Ahmad Khairi Hassan; Norashikin Abdul Moris; Noor Nasuha Noor Hamal; Nurul Ain Amidar; Mohd Azlan Rusdi (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 03-2021) [August 2021]